Analisis Penilaian Kinerja Pada Dinas Perumahan Rakyat dan Kawasan Permukiman (Perkim) Kota Madiun Terhadap Akuntabilitas Publik Tahun 2017 - 2020 - Herry Purnomo; Siti Suharni; Erry Sari (JAMER : Jurnal Akuntansi Merdeka, 2022)
The objectives of the research are (1). Determine the effect of the stakeholders perspective on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City from 2017 to 2020; (2). Determine the effect of the customer's perspective on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City from 2017 to 2020; (3). Determine the effect of the internal business process perspective on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City from 2017 to 2020; (4) Determine the effect of innovation and growth perspective on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City from 2017 to 2020; and (5). All perspective of balanced scorecard on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City from 2017 to 2020. This type of research is a quantitative research. Data collection techniques using questionnaires and documentation. The analysis technique uses multiple linear regression. The results of the research analysis obtained indicate that (1). There is a significant influence on the financial perspective on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City from 2017 to 2020; (2). There is a significant influence on the customer's perspective on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City in 2017 to 2020; (3). There is a significant effect on internal business process perspective on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City in 2017 to 2020, and (4). There is a significant influence on the perspective of innovation and business growth on public accountability at the Dinas Perumahan Rakyat dan Kawasan Permukiman of Madiun City in 2017 to 2020.